Occurrence of Naegleria fowleri and faecal indicators in sediments from Lake Pontchartrain, Louisiana. (11th March 2022) - A. Shahin, Shalina; H. Alarcon, Joshua; Brosky, Hanna N.; Lamori, Jennifer G.; Dada, Ayokunle C.; Xue, Jia; Gyawali, Pradip; P. Sherchan, Samendra
Abstract: The occurrence of amoeba, Naegleria fowleri, in sediment samples from Lake Pontchartrain in Louisiana was investigated. This amoeba is pathogenic and can cause primary amoebic meningoencephalitis. In this study, quantitative polymerase chain reaction methods were used to test for the prevalence of Naegleria fowleri, HF183, and E. coli . N. fowleri was detected in 51.25% of our sediment samples. Illumina sequencing of sediment samples revealed ten different phyla, with Cyanobacteria being the most predominant at sites that generally presented with the highest median N. fowleri concentrations. N. fowleri was however strongly negatively correlated with HF183 ( r = −0.859, p < 0.001). Whenever sediment E. coli concentrations were below 1.54 Log GC/g, there was only a 37.5% chance that N. fowleri would be detected in the same sample. When sediment E. coli concentrations exceeded 2.77 Log GC/g, the chances of detecting N. fowleri in the same sample increased to 90%, potentially suggesting predatory activity by the amoeba. The effect of temperature was observed to be different in relation to observed N. fowleri concentrations and detection rates. Although sediment samples collected during periods of higher temperatures had significantly lower mean N. fowleri concentrations (2.7 Log GC/g) compared to those collected at lower temperatures (3.7 Log GC/g, t (39) = 4.167, p < 0.001), higher N. fowleri detection rates in the overall samples were observed at higher temperatures (>19.1 °C) than at lower temperatures (<19.1 °C). HIGHLIGHTS: The occurrence of free-living amoeba, Naegleria fowleri in sediment samples from Lake Pontchartrain in Louisiana was investigated. N. fowleri was detected in 51.25% of our sediment samples. N. fowleri was, however, strongly negatively correlated with HF183 ( r = −0.859, p < 0.001). Higher N. fowleri detection rates were observed at higher temperatures than at lower temperatures.